Pressure-induced transition from wavy circular to ring-shaped buckles. (15th August 2021) - Yu, Sen-Jiang; Parry, Guillaume; Coupeau, Christophe; Li, Lingwei
Graphical abstract: Abstract: We report on buckling structures observed on tantalum films deposited by sputtering on silicon wafers. It is shown that, above a critical diameter, the circular blisters evolve to ring-shaped buckles, whatever the smooth or undulating type of their edges. The experimental results have been compared to finite element simulations. In particular, the polygonal collapsed part at the center of the buckles can be well understood by taking into account the pressure mismatch between the inside and outside parts of the buckles.